Iron-wüstite revisited: A revised calibration accounting for variable stoichiometry and the effects of pressure. (15th November 2021) - Hirschmann, M.M.
Abstract: We present thermodynamic and empirical calculations for the iron-wüstite (IW) buffer applicable from 100 kPa to 100 GPa and from 1000 to 3000 K. The thermodynamic calculation self-consistently accounts for changing stoichiometry of iron-saturated wüstite as a function of temperature and pressure. In contrast to some previous models for calculating IW at high pressure, the model incorporates a thermodynamically valid representation of the free energy of stoichiometric FeO at 100 kPa. Earlier high pressure models that relied on the JANAF thermochemical tables (Chase, 1998 ) were compromised because JANAF has erroneous values for the properties of FeO. This resulted in predicted oxygen fugacities buffered by IW that are between 0.2 and 1.1 log units too reducing at 3000 and 1000 K, respectively. The revised thermodynamic calculations indicate that iron-saturated wüstite becomes more nearly stoichiometric with increasing pressure, but that this shift depends on temperature. Near-stoichiometric FeO ( y < 0.01, for Fe1-y O) is reached close to 8 GPa at 1000 K and 17 GPa at 2000 K. An empirical function is presented that accurately reproduces the thermodynamic calculation and facilitates easy quantification of the f O2 of IW over the full range of temperatures and pressures covered by the model. Some caution is warranted in calculation of IW at high pressures, after FeO undergoes a transition from an insulator to a conductor and where low spin Fe 2+ is stabilized, as the present model does not incorporate the effects of these transitions on the IW buffer.